The plastid and mitochondrial genomes of Vavilovia Formosa (Stev.) Fed. and the phylogeny of related legume genera - N. V. Shatskaya; V. S. Bogdanova; O. E. Kosterin; G. V. Vasiliev; A. K. Kimeklis; E. E. Andronov; N. A. Provorov (Вавиловский журнал генетики и селекции)
The plastid and mitochondrial genomes of Vavilovia formosa (Stev.) Fed. were assembled on the base of the data of high-throughput sequencing of DNA isolated from a sample from North Osetia, Russia, using Illumina and PacBio platforms. The long PacBio reads were sufficient for reliable assembling organellar genomes while the short Illumina reads obtained from total DNA were unacceptable for this purpose because of substantial contamination by nuclear sequences. The organellar genomes were circular DNA molecules; the genome of mitochondria was represented by two circular chromosomes. A phylogenetic analysis on the basis of plastid genomes available in public databases was performed for some representatives of the tribes Fabeae, Trifolieae and Cicereae. As was expected, the V. formosa branch proved to be sister to the Pisum branch, and the tribe Fabeae was monophyletic. The position of Trifolium L. appeared sensitive to the phylogeny reconstruction method, either clustering with Fabeae or with the genera Medicago L., Trigonella L. and Melilotus Mill., but the internodes between successive divergences were short in all cases, suggesting that the radiation of Trifolium, other Trifolieae and Fabeae was fast, occurring within a small time interval as compared to further evolution of these lineages. The data on the relatedness of the plastid genomes of Trifolium and Fabeae correlate with the similarity of N2-fixing symbionts in these legumes represented by Rhizobium leguminosarum biovars trifolii and viciae, while the symbionts of Medicago, Melilotus and Trigonella belong to the Sinorhizobium meliloti and S. medicae species, which are distant from Rhizobium.